Exercise-Induced Rhabdomyolysis and Stress-Induced Malignant Hyperthermia Events, Association with Malignant Hyperthermia Susceptibility, and RYR1 Gene Sequence Variations - Antonella Carsana (The Scientific World Journal)
Exertional rhabdomyolysis (ER) and stress-induced malignant hyperthermia (MH) events are syndromes that primarily afflict military recruits in basic training and athletes. Events similar to those occurring in ER and in stress-induced MH events are triggered after exposure to anesthetic agents in MH-susceptible (MHS) patients. MH is an autosomal dominant hypermetabolic condition that occurs in genetically predisposed subjects during general anesthesia, induced by commonly used volatile anesthetics and/or the neuromuscular blocking agent succinylcholine. Triggering agents cause an altered intracellular calcium regulation. Mutations in RYR1 gene have been found in about 70% of MH families. The RYR1 gene encodes the skeletal muscle calcium release channel of the sarcoplasmic reticulum, commonly known as ryanodine receptor type 1 (RYR1). The present work reviews the documented cases of ER or of stress-induced MH events in which RYR1 sequence variations, associated or possibly associated to MHS status, have been identified.